عزوف طلبة التربية البدنية والرياضية عن المحاضرات - رباحي محمد ابو لقاسم; لشهب عبد الحكيم; حنة الهاشمي (My University, 2020)
ىدفت ىذه الد ا رسة إلى معرفة الدور الذي يمعبو عزوؼ الطالب الجامعي وخاصة طمبة معيد - العمو والتقنيات الانشطة البدنية والرياضية عف حظور المحاض ا رت واثره عمى التحصيؿ الجامعي، - وتسميط الضوء عمى الاطار العا عمى ىذه الظاىرة وتحديد القواعد الرئيسية ليا ومعرفة مدى تأثيرىا أو قدرتيا في الحياة الجامعية لمطمبة وتحصيمي العممي. وذلؾ مف خلاؿ تحميؿ معمؽ ليا، وتناولنا جانبا آخر مف الد ا رسات السابقة التي كانت في سياؽ موضوعنا. وقمنا بتحديد عينة لتطبيؽ د ا رستنا عمييا تمثمت في مجموعة مف طمبة المعيد وت توزيع استما ا رت الاستبياف عمى أف ا رد العينة ليت بذلؾ الحصوؿ عمى 32 نسخة صالحة لمتحميؿ الاحصائي، لنقو بعدىا بتحميميا بواسطة برنامج الحزمة الاحصائية SPPS مف أجؿ الحصوؿ عمى نتائج لد ا رستنا. وكانت أى النتائج المتوصؿ ليا ىي كثرة الواجبات والظروؼ العائمية كانت مف اى الاسباب التي تجعؿ مف طالب معيد الرياضة اف يعزؼ ويغيب عف حضور المحاض ا رت، بالإضافة الى مشاكؿ الحياة الجامعية واثرىا عمى نفسية الطالب كالنقؿ الجامعي وبعد الجامعة عف سكف الطالب
دراسة ميدانية بمعهد علوم وتقنيات الأنشطة البدنية والرياضية بالأغواط
This study aimed to know the role played by the university student and their absences - especially students of the Institute of Science and Technology, Physical and Sports Activities - from the attendance of lectures and its effect on university achievement, and to shed light on the general framework on this phenomenon and to define the main rules for it and to know the extent of its impact or ability in the university life of students And their educational attainment. And that is through an in-depth analysis of it, and we have dealt with another aspect of previous studies that were in the context of our study. We selected a sample to apply our study to, represented by a group of the institute's students. Questionnaire forms were distributed to the sample members in order to obtain 32 copies valid for statistical analysis, and then we would analyze them by the SPPS statistical package in order to obtain the results of our study. The most important results obtained were the abundance of duties and family circumstances, which were among the most important reasons that make a student of the Sports Institute to play and be absent from attending lectures, in addition to the problems of university life and their impact on the student’s psyche, such as university transportation and the distance from the university from the student’s residence.